Perencanaan Strategis Sistem Informasi Pada UMKM Bened Dalam Menghadapi Masa Pandemi Covid-19 - Eldad, Daniel Benedictus; Tanaem, Penidas Fiodinggo (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
UMKM Bened is one of the UMKM engaged in the culinary field. During the COVID-19 pandemic, economic activity in Indonesia decreased, this was a negative impact for UMKM. Advances in infomation technology can be utilized so that business activities can continue during the COVID-19 pandemic. Strategic planning of information systems is needed so that UMKM Bened can implement the righy IS/IT. This study uses the ward and peppard method in data collection and the preparation of strategic planning for information systems. The tools usesd are SWOT analysis, and portofolio application by applying the McFarlan Strategic Grid and then there is a proposed information system. The results of the IS/IT strategic planning research on UMKM Bened is a UMKM Bened website/ Where this website can later improve business processes so that they are more effective and efficient. So that UMKM Bened can remain competitive during the COVID-19 pandemic.